Case report: POEMS syndrome masquerades as diabetic foot - Zhou, Guang-Xin; Xiao, Li; Bi, Yong-Min; Yang, Fen; Yang, Cai-Zhe; Zhang, Da (Frontiers in Neurology, 2024)
We present the case of a 54-year-old woman with reasonable blood sugar control who presented with a diabetic foot combined with severe peripheral neuropathy and vascular disease. Lower limb muscle weakness, muscle atrophy, skin pigmentation, and emaciation were also observed. Although her muscle strength improved after glucocorticoid treatment, it remained challenging to account for the other symptoms in this particular patient with chronic inflammatory demyelinating polyneuropathy. Plump liver and spleen, hidden bone lesions combined with seemingly unexplained cerebral infarction, and serous effusion led us to suspect polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome. The abnormal proliferation of monoclonal plasma cells and a significant increase in vascular endothelial growth factor (VEGF) levels confirmed the diagnosis of POEMS syndrome. After 1 month of treatment with lenalidomide and dexamethasone, the diabetic foot ulcers healed, and the symptoms of myasthenia and fatigue improved. Diabetic feet may represent only the tip of the iceberg of an underlying POEMS syndrome. Our report aimed to increase awareness of this rare yet significant situation, advocating for the prompt identification and treatment of POEMS syndrome.